Mean soup - Everitt, Betsy (San Diego : Voyager Books/Harcourt Brace, 1992)
Horace feels really mean at the end of a bad day, until he helps his mother make Mean Soup.
"A Voyager book."
Publisher's Weekly
School Library Journal
Wilson's Children
Booklist, October 1996
Horn Book, December 1996
Keywords: Anger -- Fiction; Cooking -- Fiction; Anger -- Fiction; Cooking -- Fiction